The Obligate Symbiont “Candidatus Megaira polyxenophila” Has Variable Effects on the Growth of Different Host Species - Pasqualetti, Chiara; Szokoli, Franziska; Rindi, Luca; Petroni, Giulio; Schrallhammer, Martina (Frontiers in Microbiology, 2020)
“Candidatus Megaira polyxenophila” is a recently described member of Rickettsiaceae which comprises exclusively obligate intracellular bacteria. Interestingly, these bacteria can be found in a huge diversity of eukaryotic hosts (protist, green algae, metazoa) living in marine, brackish or freshwater habitats. Screening of amplicon datasets revealed a high frequency of these bacteria especially in freshwater environments, most likely associated to eukaryotic hosts. The relationship of “Ca. Megaira polyxenophila” with their hosts and their impact on host fitness have not been studied so far. Even less is known regarding the responses of these intracellular bacteria to potential stressors. In this study, we used two phylogenetically close species of the freshwater ciliate Paramecium, P. primaurelia and P. pentaurelia (Ciliophora, Oligohymenophorea) naturally infected by “Ca. Megaira polyxenophila”. In order to analyse the effect of the symbiont on the fitness of these two species, we compared the growth performance of both infected and aposymbiotic paramecia at different salinity levels in the range of freshwater and oligohaline brackish water i.e. at 0, 2, and 4.5 ppt. For the elimination of “Ca. Megaira polyxenophila” we established an antibiotic treatment to obtain symbiont-free lines and confirmed its success by fluorescence in situ hybridization (FISH). The population and infection dynamics during the growth experiment were observed by cell density counts and FISH. Paramecia fitness was compared applying generalized additive mixed models. Surprisingly, both infected Paramecium species showed higher densities under all salinity concentrations. The tested salinity concentrations did not significantly affect the growth of any of the two species directly, but we observed the loss of the endosymbiont after prolonged exposure to higher salinity levels. This experimental data might explain the higher frequency of “Ca. M. polyxenophila” in freshwater habitats as observed from amplicon data.